Exploring the effect of conflict towards self-managed project teams (SMPTs) - Zaleha Yazid, (Universiti Kebangsaan Malaysia, 2011)
The aim of this article is to explore the effect of conflict within Self-Managed Project Team (SMPT) in Small and Medium Sized Firms specifically in Malaysia. Literature suggests that the implementation of SMPT not only increases productivity in organizations but also contributes towards increasing employees’ involvement as the team is being managed by the team members rather than a formal leader who exists within the team. Thus, it is crucial for organizations to create understanding on how conflict is managed in SMPTs in order to ensure the successfulness of this particular type of team.